Exploring Tradeoff between Distance-Minimality and Diversity of Landing Routes for Aircraft Landing Optimization - Akinori Murata; Hiroyuki Sato; Keiki Takadama (SICE Journal of Control, Measurement, and System Integration, 2018)
This paper focuses on the aircraft landing problem (ALP) and proposes an optimization method for ALP which addresses both the landing routes of multiple aircraft and their landing sequence. The difficulty of solving ALP is to optimize both the landing route and landing sequence of multiple aircraft, even the landing routes of the aircraft may be in conflict. To address this issue, this paper proposes a novel efficient search optimization method based on novelty search, which considers a tradeoff relationship between distance-minimality (i.e., a short route of an aircraft) and diversity (i.e., a variety of landing routes of an aircraft). Through the intensive simulation on a simplified model of Haneda Airport in ALP, the following implications have been revealed: (1) The proposed method succeeded to minimize the total distances of all aircraft while optimizing the landing routes of each aircraft with keeping a diversity of its landing routes, in comparison with the single objective method based on the fitness as distance-minimality or the novelty as diversity: and (2) ven in the aircraft crowded situation, our proposed method could find feasible solutions in all trials, while the fitness- or novelty-based single objective methods could not find them.